Sintesis Senyawa Turunan Amoksilin Dan Uji Aktivitas Antibakterinya Terhadap Bakteri Salmonella typhi - Hadi Barru Hakam Fajar Siddiq; Dewi Rashati; Dewi Riskha Nurmalasari (MPI (Media Pharmaceutica Indonesiana), 2018)
The synthesis of amoxicillin derivate has been done by reacting amoxicillin with 4-t-butylbenzoil chloride. The product was characterized by organoleptic test, melting point determination, TLC, UV/Vis Spectrophotometry, and FTIR Spectrophotometry. Antibacterial activity of amoxicillin derivative against Salmonella typhi were tested using dilution method. Result showed that the product has characteristic as follow: light yellow powder, bitter bite, melting point of 132 °C, Rf value of 0.86, pH value of 7.7, maximum wavelength (uv) of 286 nm. Moreover, FTIR spectra of amoxicillin derivate exhibited peaks at 3271 cm-1 (-NH amine), 2962 cm-1 (-CH aromatic), 1633 cm-1 (-C=O ketone), and other. Antibacterial test showed that amoxicillin derivate was unable to form a clear zone around the disc paper. Amoxicillin derivate cannot be used for the treatment of Salmonella typhi.